ASSESSMENT OF WATER QUALITY INDEX OF A STRETCH OF RANIKHOLA RIVER, EAST SIKKIM - G.S. YUREMBAM,; S. GURUMAYUM,; C. HAOBAM,; S. CHOWDHURY, (The Bioscan, 2020)
The study was conducted to assess the Water Quality Index (WQI) of a stretch of the Ranikhola river of East Sikkim. The WQI values were calculated using weighted arithmetic water quality index method. The overall Water Quality Index value degraded as the river traverses from the upstream section (L1) towards the downstream section (L5). The WQI values of the five sampling stations (L1-L5) for Post Monsoon seasons were recorded as 10.45, 52.64, 53.05, 56.43 and 57.86 respectively with an average value of 46.08. Likewise, the Monsoon season recorded values were 25.27, 42.15, 53.05, 57.22 and 54.60 respectively with an average value of 46.45. The presence of densely populated residential homes in the adjoining areas of sampling stations L2 to L5 and sand mining activities has influenced the physico-chemical parameters of water samples. WQI values at these stations deteriorate as the river flows from upper reaches to urbanized/ downstream area. The main causes of deterioration in water quality are anthropogenic activities, soil erosion, discharge of untreated sewage, and polluted urban runoffs. The present water quality status indicates the necessity to adopt suitable management policy, regulate human activities and implement conservation efforts along the stretch of the Ranikhola river.